Hydroxyapatite Prepared by Co-Precipitation with Calcium Carbonate: Effects of Digested Calcium Carbonate and Phosphate Sources - Suksomrana, Wallika; Molloy, Robert (Asian Health, Science and Technology Reports, 2017)
The Hydroxyapatite (HAP) was prepared by co-precipitation of calcium carbonate (CaCO3) with various orthophosphate sources such as phosphoric acid (H3PO4), ammonium dihydrogen phosphate (NH4H2PO4) and diammonium hydrogen phosphate ((NH4)2HPO4) under ambient conditions. CaCO3was digested by 20% HNO3 to produce calcium cation which reacted with the orthophosphate ion to form hydroxyapatite. All XRD patterns closely matched with the HAP reference data. There was no change in the sharpness of the diffraction peaks and little or no change in the peak intensity was observed when compared to various phosphate sources (H3PO4, NH4H2PO4and (NH4)2HPO4). The FTIR spectrum showed without the characteristic bands of B-type CO32- substitution at 1421–1473 cm-1 (v3) and 874 cm-1(v2). Moreover, the FTIR spectrum showed without the characteristic peak of A-type CO32-substitution at 1540 cm-1. The precipitation of HAP from digested CaCO3 solution occurred at 3 hours, while the reaction from non-digested CaCO3 solution occurred at 18 hours. The digestion of CaCO3 reduced the preparation time of HAP and also decreased the CO32-substitution in HAP.